Neurofibromatosis type 1 in a patient with a unique c.1369_1370insGGGTC mutation in the NF1 gene - Rustam N. Mustafin (Pediatric Hematology/Oncology and Immunopathology, 2026)
Neurofibromatosis type 1 (NF1) is a severe monogenic disorder characterized by café-au-lait spots and neoplastic lesions, including plexiform neurofibromas that are treated with targeted therapy using a mitogen-activated protein kinase inhibitor. A sporadic case of NF1 caused by a unique, previously unreported NF1 gene mutation, c.1369_1370insGGGTC(p.H457fs), was identified in a 13-year-old boy. The features of NF1 in the patient included early manifestation of tumor syndrome with simultaneous development of cutaneous neurofibromas, tumors of spinal roots, vagus nerve and plexiform neurofibromas, cognitive and speech impairment, growth retardation, and multiple skeletal abnormalities. At the age of 10, targeted therapy was initiated, resulting in a significant tumor size reduction and thus indicating the effectiveness of this approach in NF1 caused by this pathogenic NF1 variant.